El cuerpo como significante en la producción artística - Riofrío Rogel, Sara Yomaira (2016)
The present research aims to address a social problem deeply rooted in different times, and that has great media importance in different spheres, social, economic and cultural. We refer to "Fashion and its influence on the processes of cultural identity from contemporary art". We hold that those who integrate society, are part of a cultural construct, which is influenced by a number of constraints or impositions of all kinds, ie stereotypes, taboos, prejudices; That undermine our own identity and therefore our own personality. We are constituted as contemporary urban tribes that we raise our prejudices, flaunt our whims and vanities, and identify ourselves with ideals and slogans in this society, giving an excessive importance to everything that comes from abroad, and we cease to be unique, we lose all vestige Of originality. Our contribution lies in the visualization from a critical-reflexive perspective, in the construction of our artistic production, from the new poetics of the artistic language, new materials and supports in the material construction of our work. Artistic production at the local level has left us empty in the treatment of themes that link a criticism to the representation of the body, taking it as an object of consumption, but not, as an enhancer of meanings. It is worth mentioning that in the research process, artistic practices were taken as direct referents from the object art and other contemporary productions that have taken as a questioning element of a reality to the body, until one can find in the national context artistic references that of one or the other This way they incorporate to their artistic work critical reflections around the body as a container of meanings, and place it as a fundamental pillar of their production. Through experimental research methodologies, it was possible to generate artistic proposals that placed the body at the local level, its uses and abuses in society as a center of reflection, to convert it into an artistic object, which is capable of symbolically challenging the Reality that revolves around the body. Undoubtedly, what has been experienced in the present research has expanded the range of possibilities not only in artistic representation, but also in tackling social problems that currently occur, favoring in a considerable way the local production that is gradually increasing The ways of seeing and doing art. To this extent, the artistic proposal seeks to insert itself into the collective imagination with a questioning discourse, the result of a critical posture and the lifting of information obtained from the reality itself, which is the fundamental basis for artistic production, and even more so in contexts such as Which is imperative to generate new artistic proposals that refresh the landscape of the arts. In this way the research concludes with the work "Perfecta" giving rise to a symbolic construction that allows to reflect from the artistic object the current problematic, where the work alludes to the loss of personal identity, becoming that bridge that connects with the Society through artistic representation.